ANALISIS DAMPAK SISWA YANG NAIK KELAS BERSYARAT TERHADAP KUALITAS PEMBELAJARAN KELAS XI DI MADRASAH ALIYAH DARUL HUDA PUSAT MANDALAWANGI - Anisa, Anisa; Royhatudin, Aat; Hidayat, Ahmad; Kosim, Nandang (Staisman Press, 2023)
This research aims to determine the impact of students who are conditionally promoted to the quality of learning at Madrasah Aliyah Darul Huda, Mandalawangi Center. This research was carried out during for one month, starting on 24 July-23 August 2023. This research method uses qualitative methods, including observation, interviews and documentation. Based on the results of this research, students who are promoted conditionally have an impact on the school, community, environment and especially have a negative impact on themselves. The solution from this research includes several parties, namely: Firstly, parents, parents must pay attention to their children's behavior and care about their children's education. Second, from the school side, the school must provide humanist services so that students are happy at school. If students are happy then the learning process will run conducively and the quality will increase. Not only that, the school also helped improve school discipline and order.